Pembuatan Alat Pengadukan Pupuk Kompos Berbasiskan Mikrokontroler - Roza Susanti - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
In fabrication of compos mixing machine based on microcontroller, an AC motor 1 phase used to rotate the container and it will help the farmer work in stirring and mixing compos material. In order to display the process, a LCD is use in this fabrication.The design of this machine is divided into two categories, hardware design and software design. The hardware consist of an AVRATmega 8535 microcontroller minimum system , a LCD, Keypad, an AC Motor 1 phase, a Capacitor, and a relay. In the order hand for software design, a Code vision-AVR program language as the program application. The data analysis techniques are conducted by testing the machine performs. Not only by measuring operating voltages, but also testing the microcontroller with a program application.This machine is based on microcontroller AVRATmega8535 and using C language in programming. In order to display the mixing output, time setting is displayed on LCD. The optimum result started from the first 10 seconds ON condition and the second of 10 seconds ON condition should have a 30 seconds time off.